Numerical and Experimental Study on Mode Identification Error Characteristics of Fan Noise - Xu, Kunbo; Liu, Cunliang; Tong, Fan; Qiao, Weiyang (Frontiers in Energy Research, 2022)
The influence of different test methods on the accuracy of mode identification is not clear, and it is necessary to explore the error transfer characteristics in mode decomposition of fan noise. Numerical and experimental research studies are carried out on the advantages and disadvantages of radial rake and axial microphone array and error transmission characteristics in mode decomposition. In the numerical study, the error transmission characteristics of different arrays are investigated by adding random disturbances to the artificial sound field, so as to evaluate the applicability and limitations of the two typical arrays in mode identification based on the error analysis theory. The mode recognition error of the single-stage axial flow fan is investigated experimentally using the designed radial rakes and axial arrays. The results show that although the radial rake can directly measure the radial distribution of the modal amplitude, it has a large error in the mode identification at low frequencies. Compared with the radial rake, axial array will take more priority in practical applications. The accuracy of the axial microphone array in mode recognition strongly depends on the axial spacing of the array measuring sensors. The small deviations in the mode identification when applying the two typical arrays are caused by the different signal-to-noise ratio of the sound pressure signals acquired by the two arrays and their discriminative sensitivities to the duct airflow. Based on the obtained modal identification error characteristics, an effective mode identification method can be proposed to help fan noise reduction design.